Effects of low- and high-volume stretching on bench press performance in collegiate football players - Molacek, Z. D.; Conley, D. S.; Evetovich, T. K.; Hinnerichs, K. R. (The Journal of Strength and Conditioning Research, 2010)
The purpose of this study was to determine the effects of acute low- and high-volume static and proprioceptive neuromuscular facilitation (PNF) stretching on 1-repetition maximum (1RM) bench press. Fifteen healthy male National Collegiate Athletic Association Division II football players (age: 19.9 ± 1.1 years; weight: 98.89 ± 13.39 kg; height: 184.2 ± 5.7 cm; body composition: 14.6 ± 7.4%; and 1RM bench press: 129.7 ± 3.3 kg) volunteered to participate in the study. Subjects completed 5 different stretching protocols integrated with a 1RM dynamic warm-up routine followed by 1RM testing in randomly assigned order. The protocols included (a) nonstretching (NS), (b) low-volume PNF stretching (LVPNFS), (c) high-volume PNF stretching (HVPNFS), (d) low-volume static stretching (LVSS), and (d) high-volume static stretching (HVSS). Two and 5 sets of stretching were completed for the low- and high-volume protocols, respectively. The stretching protocols targeted triceps and chest/shoulder muscle groups using 2 separate exercises. There were no significant differences in 1RM bench press performance (p > 0.05) among any of the stretching protocols NS (129.7 ± 3.3 kg), LVPNFS (128.9 ± 3.8 kg), HVPNFS (128.3 ± 3.7 kg), LVSS (129.7 ± 3.7 kg), and HVSS (128.2 ± 3.7 kg). We conclude that low- and high-volume PNF and static stretching have no significant acute effect on 1RM bench press in resistance-trained collegiate football players. This suggests that resistance-trained athletes can include either (a) a dynamic warm-up with no stretching or (b) a dynamic warm-up in concert with low- or high-volume static or PNF flexibility exercises before maximal upper body isotonic resistance-training lifts, if adequate rest is allowed before performance.